Sedimentological and ichnological implications of rapid Holocene flooding of a gently sloping mud‐dominated incised valley – an example from the Red River (Gulf of Tonkin). Issue 5 (27th March 2017) - Wetzel, Andreas; Szczygielski, Agata; Unverricht, Daniel; Stattegger, Karl
Abstract: The Gulf of Tonkin coastline migrated at an average rate of ca 60 m year −1 landward during Holocene sea‐level rise (20 to 8 ka). Due to a combination of rapid coastline migration and undersupply of sand, neither coastal barriers nor tidal sand bars developed at the mouth of the Red River incised valley. Only a 30 to 80 cm thick sandy interval formed at the base of full‐marine deposits. Thus, the river mouth represented a mud‐dominated open funnel‐shaped estuary during transgression. At the base of the valley fill, a thin fluvial lag deposit marks a period of lowered sea‐level when the river did not reach geomorphic equilibrium and was thus prone to erosion. The onset of base‐level rise is documented by non‐bioturbated to sparsely bioturbated mud that occasionally contains pyrite indicating short‐term seawater incursions. Siderite in overlying deposits points to low‐salinity estuarine conditions. The open funnel‐shaped river mouth favoured upstream incursion of seawater that varied inversely to the seasonal strongly fluctuating discharge: several centimetres to a few tens of centimetres thick intervals showing marine or freshwater dominance alternate, as indicated by bioturbational and physical sedimentary structures, and by the presence of Fe sulphides or siderite, respectively. Recurrent short‐term seawater incursions stressed the burrowing fauna. The degree of bioturbation increases upward corresponding to increasing marine influence. The uppermost estuarine sediments are completely bioturbated. The estuarine deposits aggraded on average rapidly, up to several metres kyr −1 . Siphonichnidal burrows produced by bivalves, however, document recurrent episodes of enhanced deposition (>0·5 m) and pronounced erosion (<1 m) that are otherwise not recorded. The slope of the incised valley affected the sedimentary facies. In steep valley segments, the marine transgressive surface (equivalent to the onset of full‐marine conditions) is accentuated by the Glossifungites ichnofacies, whereas in gently sloped valley segments the marine transgressive surface is gradational and bioturbated. Marine deposits are completely bioturbated.